The Influence of Implementing P5 in the Merdeka Curriculum with Entrepreneurship Themes and Entrepreneurial Attitudes on Entrepreneurial Interest - Mutiara Agista Gunawan Putri; Dhiah Fitrayati (Universitas Negeri Padang, 2024)
This study has the objective to examine the impact of implementing P5 Entrepreneurship Themes and entrepreneurial attitudes on students' entrepreneurial interests. It employs a quantitative approach and a causal associative design. The primary data source consists of ordinal data gathered through a questionnaire. A sample of 161 students was selected using the Slovin formula, representing all class XI students who participated in P5 Entrepreneurship Theme activities as the population. Data analysis employs multiple linear regression analysis conducted using SPSS 26. The findings from both partial and simultaneous analyses indicate that the implementation of P5 Entrepreneurship Themes and entrepreneurial attitudes significantly influence students' entrepreneurial interests.